Understanding tourists´ economizing strategies during the global economic crisis - Campos-Soria, Juan Antonio; Inchausti-Sintes, Federico; Eugenio-Martin, Juan Luis (My University, 2014)
This paper explores how tourists from 165 regions of EU-27 countries cut back their tourism expenditure during the global economic crisis in 2009. This study disentangles the cutback tourism expenditure in two mutually related decisions: First, it takes into account whether the tourist has had to cut back on tourism expenditure due to the crisis and second, how they decided to cut back according to six alternatives: “fewer holidays”, “reduced length of stay”, “cheaper means of transport”, “cheaper accommodation”, “travel closer to home” or “change the period of travel”. The econometric model able to deal with such simultaneous decisions is an adaptation of the Heckman model in generalized structural equations modeling. This methodology permits to control by sample selection bias and correlations between equations. This paper highlights the existence of patterns in the cut back alternatives depending on the socioeconomic characteristics of the household and the climate conditions in origin.
Keywords: Turismo; Crisis económicas; Tourism expenditure; Economizing strategies; Economic crisis; Generalized structural equations modelling; Regional studies